Clinical significance of aberrant vimentin expression in oral premalignant lesions and carcinomas. (19th July 2013) - Sawant, SS; Vaidya, MM; Chaukar, DA; Alam, H; Dmello, C; Gangadaran, P; Kannan, S; Kane, S; Dange, PP; Dey, N; Ranganathan, K; D'Cruz, AK
<x xml:space="preserve">Abstract</x> Objective To investigate the clinical significance of vimentin expression at early and late events of tobacco/areca nut–associated oral tumorigenesis. Materials and Methods Immunohistochemistry (IHC) was carried out on paraffin‐embedded tissues of oral mucosa normal (n = 10), inflammatory lesions (n = 19), leukoplakia (n = 52), submucous fibrosis (n = 71) and tumours/cut margins (n = 227 each), using anti‐vimentin antibody, and the expression profile was correlated with patients' clinical parameters. Immunofluorescence, Western blot and RT‐PCR analysis were also carried out wherever adequate and fresh tissues were available. Results Aberrant vimentin expression was seen in hyperplastic, dysplastic and fibrotic tissues, which showed statistically significant correlation with the histopathological grade of dysplasia (P = 0.001) and fibrosis (P = 0.009). Vimentin expression also showed statistically significant correlation with tumour size (P = 0.048), clinical stage (P = 0.013), regional lymph node metastases (P = 0.001), local recurrence (P = 0.001) and survival (P = 0.021) of patients with oral squamous cell carcinoma (OSCC). Its expression in invasive fronts statistically correlated with development of nodal metastasis and local recurrence. Conclusions Our results suggest possible role of vimentin in early events of tobacco/areca nut–associated oral tumorigenesis, which may prove useful to predict the malignant potential of high‐risk oral lesions. Further, association between vimentin expression in invasive fronts and aggressive phenotype of tumours may help clinicians to choose the appropriate treatment modality for OSCC management.